Concomitant use of clopidogrel and proton pump inhibitors: impact on platelet function and clinical outcome- a systematic review. Issue 8 (31st July 2012) - Focks, Jeroen Jaspers; Brouwer, Marc A; van Oijen, Martijn G H; Lanas, Angel; Bhatt, Deepak L; Verheugt, Freek W A
Abstract : Background: Clopidogrel as an adjunct to aspirin has improved outcomes after acute coronary syndromes, but laboratory studies suggest a reduced antiplatelet effect when proton pump inhibitors (PPIs) are co-administered. Despite corroborating data from retrospective studies, new clinical data fuel the controversy on this issue. Purpose: Systematic review of the impact of the addition of PPIs to clopidogrel on platelet function and cardiovascular outcome. Data sources: PubMed, Web-of-Science, Cochrane Database and reference lists of related articles. Study selection: Published articles on controlled studies addressing the addition of PPIs to clopidogrel. Platelet function studies describe patients as well as healthy volunteers. Clinical studies concern patients using clopidogrel for acute coronary syndromes or because of stent implantation for stable coronary disease. Data extraction: Two investigators independently reviewed the identified articles for eligibility, and one author extracted the data. Data synthesis: In 70% (7/10) of the laboratory studies examining healthy volunteers on clopidogrel, addition of PPIs resulted in a significant reduction in platelet inhibition. For patients, this was observed in 11/18 (61%) studies. The 33 clinical studies showed significant heterogeneity in observed outcomes, with risk ratios for major adverse cardiovascular events varying from 0.64 to 4.58 in the case of PPI use, which was randomly allocated in only two studies. Consequently, imbalances between prognosticators at baseline and PPI prescription bias markedly contributed to the variability in results. Conclusions: Despite indications of reduced antiplatelet activity ex vivo in the case of PPI administration in clopidogrel users, data on the clinical consequences are controversial. With the accumulating evidence from better designed, prospective clinical studies, an adverse effect of PPI use on clinical outcome in patients on clopidogrel cannot be substantiated. This review challenges the validity of conclusions based on quantitative analyses of predominantly non-randomised data.